Endovascular Treatment of Giant Celiac Artery Aneurysm in Behcet's Disease. (May 2021) - Dwivedi, Arika; Wayne, Erik; Sangroula, Daisy; Sigdel, Abindra
We report a case of a 17-year-old male with Behcet's disease (BD) with giant celiac artery aneurysm and impending rupture. Over the past 8 weeks, patient began having intermittent back and abdominal pain that worsened and became persistent over the past few days. This was accompanied by anorexia and non-bilious vomiting. Computed tomography angiogram (CTA) demonstrated a wide neck large celiac artery aneurysm (60 mm diameter). Endovascular repair of the aneurysm was performed using stent graft of the aorta and transcatheter coil embolization of the aneurysm sac. Technical success was confirmed by interruption of flow in the aneurysm, and preservation of distal native circulation at the conclusion of the procedure. One-week post-embolization, a CTA demonstrated complete thrombosis of the aneurysm. On follow-up CTA at 3, 6, and 12 months after embolization, the aneurysm has completely thrombosed and decreased in size to 24 mm. Patient remains asymptomatic till date.